1989
DOI: 10.1111/j.1399-0004.1989.tb02927.x
|View full text |Cite
|
Sign up to set email alerts
|

Fryns syndrome: report on 8 new cases

Abstract: The name Fryns syndrome was given to a new variable multiple congenital anomaly syndrome, almost always lethal, described in 1978, and now known to be autosomal recessive. Since that date, 20 patients have been reported in the literature. We describe 8 new cases, 6 of which were diagnosed in a series of 112276 consecutive births (livebirths and perinatal deaths). The prevalence of this syndrome can be estimated to be around 0.7 per 10000 births. These new cases confirm that the most frequent anomalies are diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 9 publications
0
15
0
6
Order By: Relevance
“…Fryns syndrome may be the most common autosomal recessive syndrome in which congenital diaphragmatic hernia is a cardinal feature (Aymé et al, 1989;Slavotinek et al, 2005). Vargas et al (2000) reported a pair of monozygotic twins with Fryns syndrome discordant for severity of diaphragmatic defect.…”
Section: Discussionmentioning
confidence: 99%
“…Fryns syndrome may be the most common autosomal recessive syndrome in which congenital diaphragmatic hernia is a cardinal feature (Aymé et al, 1989;Slavotinek et al, 2005). Vargas et al (2000) reported a pair of monozygotic twins with Fryns syndrome discordant for severity of diaphragmatic defect.…”
Section: Discussionmentioning
confidence: 99%
“…Digestive atresias including EA, although rare in Fryns syndrome, have been observed (Ayme et al, 1989).…”
Section: Fryns Syndromementioning
confidence: 99%
“…This case had multiple congenital anomalies detected in the ultrasound scan at 26 weeks of gestation as mentioned earlier. Ayme et al (1989) 5 reported prenatal diagnosis of fryns syndrome by an ultrasound scan, between 24 and 27 weeks of gestation. Fryn syndrome was diagnosed in the prenatal ultrasound scan by detection of diaphragmatic hernias and polyhydramnios by Manouvrier-Hanu et al (1996).…”
Section: Case Reportmentioning
confidence: 99%
“…3 The incidence of congenital anomalies is 1 in 838 live births in Malaysia. 4 Fryns syndrome is a rare autosomal recessive disorder with an estimated prevalence of about 0.7 per 10,000 births in France (Ayme et al 1989). 5 Ayme et al (1989) reported prenatal diagnosis of fryns syndrome by an ultrasound scan, between 24 and 27 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation